Os “Monges de Branco” e os Sertões das Jacobinas: Catolicismo e Restauração nas ações missionárias de Pe. Alfredo Haasler. (1938/1965) - Pinheiro, Gilmara Ferreira de Oliveira (2012)
In the first half of the twentieth century, the Catholic Apostolic Roman Church moved for the Catholic restoration project started a process of restructuring its framework ecclesiastic, and reconfigured its distribution in the Brazilian space. In opposition to the Secular State that the installation of the Republic implanted, the church had the coming from European Missionary Orders to combat the proliferation of other religious beliefs and go against the Secular teaching with the creation of a large educational system that includes everything from parochial schools to universities. In Bahia, the Archbishop D. Augusto Álvares da Silva created in 1933 the diocese of Senhor do Bonfim for where he sent the young Bishop D. Hugo Bressane. He started the catholic restoration project in his diocese, beginning with the parish of Santo Antonio da Jacobina for which in 1938 brought the Cistercian Order of Mission. This started the restoration project in his catholic diocese, beginning with the parish of Santo Antônio da Jacobina in 1938 and bringing the Cistercian Order of Mission for it. The presence of this order in the region became mainly striking by the construction of the Monastery of Jequitibá, in the region of Mundo Novo, Bahia, and the construction of Cistercian priest Alfredo Haasler’s Parochial Schools in the parish of Santo Antônio da Jacobina. In less than one year, the priest began an extensive missionary work for the region: the Parish Schools that formed a network of 48 schools. Thus, this work analyzes the coming and performance of the Cistercians in the region of Jacobina, Bahia, starting from the process of Restoration of the Catholic Church.